The Web-Based Inventory Data Processing Information System At The Regional Development Planning Agency (Bappeda) North Sumatra Province - Nasution, Rukiah; Muliani, Aninda (Journal of Information Systems and Technology Research, 2022)
BAPPEDA of North Sumatra Province is one of the government agencies in charge of carrying out government affairs in the field of regional planning and development. BAPPEDA conducts inventory recording activities that are still manual with the given standardization. Weak supervision has a negative impact on management so that reporting of receipts or expenditures of goods and supervision of the use of goods is hampered. It is necessary to make improvements in the management of government-owned inventories in order to increase the effectiveness and accuracy of better data so that it does not require a long time in the processing process. Departing from these problems, a digitalized information system is needed to record inventory of goods. So, the goods data contained in the agency can be stored in the database to avoid loss and other unwanted things. This system will play a role in the goods inventory process which includes archiving goods data, ongoing goods transactions, and detailed reporting on goods at the agency. Searching data is also easier and faster because officers or employees do not need to look for archives in books or files listing items that have piled up because they can look at the inventory database at the agency. This well-digitized inventory system is expected to assist and improve services at the agency and to carry out better supervision.